ECONOMIC CONTRIBUTIONS OF TOURISM EVENTS: A MIXED-METHODS ANALYSIS OF TOMOHON INTERNATIONAL FLOWER FESTIVAL IMPACT ON LOCAL ECONOMY - Jeifer Rompas; Pingkan Maramis; Joni Kutu' Kampilong; Elsje Hanna Lintong Elsje Hanna Lintong; Gloria Wangkay; Julio Supit (SOSIOEDUKASI, 2025)
Tourism festivals are being utilized to develop local economies in developing countries, but it remains unclear whether they are effective. We conducted several pieces of research to gain a deeper understanding of this. We examined the Tomohon International Flower Festival (TIFF) and its economic impact in Tomohon. We engaged with 312 residents, business owners and tourists through the festival. For further detailed information, we conducted face-to-face interviews with 24 respondents. The study reveals that TIFF was highly beneficial to the economy. On average, the businesses made 67.4% more money, and the locals made 34.7% more. Temporary employment was approximately 1,847, and residents filled 78.9 percent of them. The average rental equilibrium in the city center was 2.8 times higher than at the outskirts (Gini coefficient = 0.487). We identified three significant factors which contribute to the degree to which the festival will generate economic benefits: the siting of the event facilities relative to the festival location, the compatibility of the festival with the local business sector and the quality of the local businesses. This paper demonstrates that tourism events can deliver numerous benefits; however, these are unevenly distributed and can exacerbate existing inequalities between regions and sectors. The results suggest that planners should design festivals to ensure that the benefits of the festivals are distributed to all members of the community. The policy demonstrates how to invite everyone to the festival simultaneously, upgrade facilities in a remote location, and provide more growth opportunities, which is essential for contributing more to the local economy.